Cost-effectiveness of a physical activity and behaviour maintenance programme on functional mobility decline in older adults: an economic evaluation of the REACT (Retirement in Action) trial - Snowsill, TM; Stathi, A; Green, C; Withall, J; Greaves, CJ; Thompson, JL; Taylor, G; Gray, S; Johansen-Berg, H; Bilzon, JLJ; de Koning, JL; Bollen, JC; et al. (Elsevier, 2022)
Background Mobility limitations in older populations have a substantial impact on health outcomes, quality of life, and social care costs. The Retirement in Action (REACT) randomised controlled trial assessed a 12-month community-based group physical activity and behaviour maintenance intervention to help prevent decline in physical functioning in older adults at increased risk of mobility limitation. We aimed to do an economic evaluation of the REACT trial to investigate whether the intervention is cost-effective.